Pengaruh Religiositas, Pendapatan dan Konsumsi Rumah Tangga terhadap Kesejahteraan Buruh Tani di Desa Payaman Kecamatan - Dwi Ayu Fitriyanti; Masruchin Masruchin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of religiosity, income and household consumption on the welfare of farm workers in Payaman Village, Solokuro District, Lamongan Regency. This study used a quantitative method by distributing questionnaires to 98 respondents of agricultural laborers in Payaman Village who were tested using SPSS software version 25. The results of this study indicate that religiosity affects the welfare of farm workers with a significant value of 0.00, income does not affect the welfare of farm workers with a significant value of 0.271 and household consumption has no effect on the welfare of farm workers with a significant value of 0.081. Then religiosity, income and household consumption simultaneously affect the welfare of farm workers with a significant value of 0.000